CAREER EDUCATION IN GENERAL EDUCATION INSTITUTIONS - Paula, Līga; Malyavina, Valeria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the research is to find out the problems and solutions of career education in primary and secondary education institutions of Zemgale planning region (ZPR). In order to achieve the aim, the following research questions were set: 1) what are the functions of career education in primary and secondary education institutions; 2) how career education is implemented in ZPR; 3) what factors positively and negatively affect implementation of career education, and 4) what are the outcomes of career education. The theoretical review of the study is based on functional structuralism and document analysis about career education. Empirical data were obtained during semi-structured interviews with representatives of schools where career education is offered. Is was concluded that the core idea of the career education is to help students to develop and realize their skills, interests and abilities, as well as to choose future profession and the most suitable educational institution. Problems related to implementation of career educations are lack of time, difficulty to organize multiple events, difficulties to plan events so they do not interfere with school work, many students are not interested in the event they have to participate in, the lack of financial resources and also the lack of career specialists in schools.